Perfecting the union : national and state authority in the US Constitution - Edling, Max M. (New York, NY : Oxford University Press, 2021)
In 'Perfecting the Union', Max M. Edling focuses on the reform of the American Union brought about by the framing and adoption of the Constitution and the resulting division of duties and powers between the national government and the states. He argues that the Constitution profoundly altered the structure of the American Union and made the federal government more effective than under the defunct Articles of Confederation, but does not accept that federal power expanded at the expense of the states.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 17, 2020).
Keywords: Constitutional law -- United States -- History; Constitutional law -- United States -- States -- History; United States -- History -- 1783-1815.; United States -- Politics and government -- 1783-1789.